Renal Cell Carcinoma with Testicular Metastases: A Case Report and Review of the Literature - Sho Yoshitake; Brian M. Shinder; Kevin Dazen; Colton Smith; Tina M. Mayer; Evita Sadimin; Eric A. Singer (Journal of Kidney Cancer and VHL, 2022)
Renal cell carcinoma (RCC) metastases to the testicle are an extremely rare clinical entity. Here, we describe the case of a man with metastatic RCC who developed a new testicular mass. Pathologic analysis after surgical removal of this testicle confirmed the diagnosis of metastatic RCC. This report highlights the unique diagnostic and therapeutic challenges associated with such a disease process.